Contribution à l’étude phytochimique et l’évaluation de l’activité antioxydante des extraits bruts et de certains composés bioactifs de Visnaga Daucoides Gaertn utilisée dans le traitement du Vitiligo - BENKORICH, FAIROUZE; BELHANAFI, AHLEM HANANE (My University, 2022)
Algeria is recognized for its varietal diversity in medicinal and aromatic plants, as well as their various popular uses in all the territories of the country. Visnaga daucoides Gaertn is a species widely used in traditional Algerian medicine for the treatment of various diseases, this is particularly the case of vitiligo which is an autoimmune disease manifested by a loss of pigment cells in the skin and which can also have impact on the quality of life of patients. The interest of this work is to determine the presence of some active compounds and the evaluation of the antioxidant potential of this species, the phytochemical screening reveals the presence of phenolic compounds flavonoids and tannins in the aqueous extract and the Quantitative analysis shows a quantity of 5.116±0.004 mg EAG/g) in total flavonoids and 1.429±0.005 mg EC/g in tannins. The evaluation of the antioxidant power is carried out by the method of the free radical DPPH indicates that the aqueous extract showed a good antioxidant efficiency with IC50 of 3,023±0,146 mg / ml which gives it to be exploited in the pharmaceutical industry.
Keywords: Vitiligo; Visnaga daucoides Gaertn; phytochemical study; antioxidant activity.